Heart rate variability biofeedback in chronic disease management: A systematic review. (August 2021) - Fournié, Claire; Chouchou, Florian; Dalleau, Georges; Caderby, Teddy; Cabrera, Quentin; Verkindt, Chantal
Highlights: Heart rate variability biofeedback is increasingly used to manage chronic symptoms. Psychological and physiological effects of HRVB have been reported in several studies. Results showed regulatory effects on autonomic function and clinical symptoms. HRVB could assist in the management of chronic patients. Abstract: Background: Heart rate variability biofeedback (HRVB) is a non-pharmacological intervention used in the management of chronic diseases. Method: A systematic search was performed according to eligibility criteria including adult chronic patients, HRVB as main treatment with or without control conditions, and psychophysiological outcomes as dependent variables. Results: In total, 29 articles were included. Reported results showed the feasibility of HRVB in chronic patients without adverse effects. Significant positive effects were found in various patient profiles on hypertension and cardiovascular prognosis, inflammatory state, asthma disorders, depression and anxiety, sleep disturbances, cognitive performance and pain, which could be associated with improved quality of life. Improvements in clinical outcomes co-occurred with improvements in heart rate variability, suggesting possible regulatory effect of HRVB on autonomic function. Conclusions: HRVB could be effective in managing patients with chronic diseases. Further investigations are required to confirm these results and recommend the most effective method.